NHLBI Cohort Studies: Opportunities for Nutrition Research (FS10-01-19). (13th June 2019) - Brown, Alison; Pratt, Charlotte; Nicastro, Holly; Aviles-Santa, Larissa; Kit, Brian; Kunz, John; Ludlam, Shari; Nelson, Cheryl; Reis, Jared; Silsbee, Lorraine; Wright, Jacqueline; Srinivas, Pothur
Abstract: Objectives: The recent release of the Strategic Plan for NIH Nutrition Research (SPNR) provides a unique opportunity for advancements in nutrition science and research through investigator-initiated efforts. This presentation provides a broad overview of the nutrition measures collected in NHLBI cohort studies and presents information on available resources through the NHLBI Biologic Specimen and Data Repository Information Coordinating Center (BioLINCC). Leveraging existing NHLBI cohort studies, which include diverse study populations, is a cost-effective approach for investigators, including early stage investigators, to develop new research questions. Methods: A landscape analysis was conducted to evaluate the nutrition measures collected in eight, multi-site NHLBI-funded cohort studies including over 163, 000 participants (ages 18 −100 y+). These datasets include the Coronary Artery Risk Development in Young Adults (CARDIA), the Framingham Heart Study, the Jackson Heart Study (JHS), the Women's Health Initiative (WHI), the Multi-Ethnic Study of Atherosclerosis (MESA), the Atherosclerosis Risk in Communities Study (ARIC), the Hispanics Community Health Study/Study of Latinos (SOL), and the Cardiovascular Health Study (CHS). Information from BioLINCC provided an additional resource to identify nutrition measures collected. Results: Most of the cohort studies used food frequency questionnaires to assess diet, with a smaller number using 24-hr recall methodology. Concentration biomarkers largely varied by study, including carotenoid and vitamin D concentrations to serum calcium and potassium levels. Lipids and blood pressure measurements were consistently collected across all cohort studies and some studies collected inflammatory markers (e.g., C reactive protein, interleukin-6) and used more invasive and costly cardiac imaging outcomes (e.g., carotid IMT, coronary calcium). Conclusions: This preliminary study identified variable nutrition measures and nutrition-related clinical outcomes in NHLBI-funded cohort studies, which are available on BioLINCC for future analysis by investigators. Additionally, these findings can help with implementation of the NIH SPNR by identifying key research gaps and possible focus areas for future research. Funding Sources: National Institutes of Health.